We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
394
1
avatar

simplify 12((3x-4)/(3)-(3-4x)/(4)-(6-2x)/(6))

 Oct 25, 2017

Best Answer 

 #1
avatar+8439 
+1

12((3x-4)/(3)-(3-4x)/(4)-(6-2x)/(6))

 

\(=\,12(\frac{3x-4}{3}-\frac{3-4x}{4}-\frac{6-2x}{6})\)

 

\(=\,\frac{(12)(3x-4)}{3}-\frac{(12)(3-4x)}{4}-\frac{(12)(6-2x)}{6} \\~\\ =\,\frac{(4)(3x-4)}{1}-\frac{(3)(3-4x)}{1}-\frac{(2)(6-2x)}{1} \\~\\ =\,(4)(3x-4)-(3)(3-4x)-(2)(6-2x) \\~\\ =\,12x-16 - 9+12x -12+4x \\~\\ =\,28x-37\)            Reduce the fractions.

 Oct 25, 2017
 #1
avatar+8439 
+1
Best Answer

12((3x-4)/(3)-(3-4x)/(4)-(6-2x)/(6))

 

\(=\,12(\frac{3x-4}{3}-\frac{3-4x}{4}-\frac{6-2x}{6})\)

 

\(=\,\frac{(12)(3x-4)}{3}-\frac{(12)(3-4x)}{4}-\frac{(12)(6-2x)}{6} \\~\\ =\,\frac{(4)(3x-4)}{1}-\frac{(3)(3-4x)}{1}-\frac{(2)(6-2x)}{1} \\~\\ =\,(4)(3x-4)-(3)(3-4x)-(2)(6-2x) \\~\\ =\,12x-16 - 9+12x -12+4x \\~\\ =\,28x-37\)            Reduce the fractions.

hectictar Oct 25, 2017

12 Online Users

avatar
avatar